Soil Microbial Activity with Depth in Claypan Soils of Southeast Kansas - C. J. Hsiao; Gretchen Sassenrath; Charles Rice; L. Zeglin; G. Hettiarachchi (Kansas Agricultural Experiment Station Research Reports, 2016)
Enzyme activities in soil indicate the relative activities of microbes, which include bacteria, fungi, algae, and other organisms. Changes in soil management alter the composition and activity of soil microbes. Plants rely on soil microbes to break down soil nutrients, and make those nutrients available for plant growth. Symbiotic relationships between soil microbes and plants enhance plant growth and productivity. Alternatively, antagonistic relationships between the soil microbial community and plants limit plant production. Soil dwellers such as nematodes or disease-causing fungi such asMacrophomina phaseolina(the fungus responsible for charcoal rot) can be particularly deleterious to crop growth and yield. Changes in the soil microbial community impact crop performance through the synergistic or antagonistic relationships between crop plants and soil biological activity. Our research is designed to explore soil microbial activity, assess changes in the potential activities of hydrolytic and oxidative enzymes involved in nutrient acquisition in the soil, and determine their potential impact on the productive capacity of soil.
Keywords: soil